Abya Yala's Indigenous and Aboriginal Women: International Agenda of Integration and Solidarity. (December 2014) - Galeano Sánchez, Lady Katherine; Werner, Meike
<x xml:space="preserve">Abstract</x> Today, the claims of Abya Yala's indigenous and aboriginal women are positioned within Latin America's indigenous agenda. This article analyzes the processes of emergence, articulation, consolidation, and integration of Abya Yala's indigenous and aboriginal women into the Continental Indigenous Women's Summit Meeting of Abya Yala, which has been held twice in the Americas, in Puno, Peru, in 2009 and in La María Piendamó, Colombia, in 2013. Through these summits, the specific claims of indigenous women have reached the international indigenous agenda and feminist and women's movements, promoting their autonomy. The article also examines the actors that favored the process of emergence, how the first and second summit meetings were held, and debates and selection of the topics. It addresses the challenges of this autonomous space managed and constituted by indigenous and aboriginal women of the continent.